The Influence Factors Of Stunting Incidents In Toddler Ages 24-59 Months At Posyandu Melati 02 - Mukhaira, Inna; Pujiningtyas, Setiarini; Nurmayanti, Selpi (Universitas Pendidikan Indonesia, 2024)
Background: Data from the Indonesian Nutrition Status Survey (SSGI) in 2022 from the Ministry of Health of the Republic of Indonesia, the national stunting rate reached 21.6% from 24.45% in 2021 and fell to 2.8%. The stunting rate in Banten Province in 2021 will decrease from 4.5% to 20% from the previous 24.5%. According to the Tenger City Health Service (DinKes), the prevalence rate of stunting in the Tangerang city area is 15.3% in 2021. The aim is to determine the factors that influence the incidence of stunting in toddlers aged 24 - 59 months at Posyandu Melati 02.Research Methods: Sampling was carried out using quantitative analytical methods with a cross sectional study design.Research Result: Analysis of the relationship between the level of maternal knowledge and the incidence of stunting as much as 69.4% and good maternal knowledge as much as 30.6%. The relationship between maternal education level and the incidence of stunting was 18.2% and higher education level was 81.8%. The relationship between economic status and the incidence of stunting is 42.9% and high economic status is 57.1%. The relationship between giving exclusive breastfeeding and the incidence of stunting is 17.6% and not giving exclusive breast milk is 82.4%.Conclusion: Maternal knowledge, maternal education level, economic status and exclusive breastfeeding greatly influence the incidence of stunting.